Constant speed control of slider-crank mechanisms: a joint-task space hybrid control approach - Flores-Campos, Juan Alejandro; Perrusquía, Adolfo; Hernández-Gómez, Luis Héctor; González, Noé; Armenta-Molina, Alejandra (Institute of Electrical and Electronics Engineers (IEEE), 2021)
In this paper, a constant speed control of slider-crank mechanisms for machine tools is proposed. A joint-task space hybrid controller based on a second-order sliding mode control and time-base generator was used to guarantee a constant speed trajectory tracking and a complete turn of the mechanism crank. A switching criterion was implemented in order to avoid the singularities located at the two extreme positions of the slider stroke. A trapezoidal speed profile with parabolic blends was designed directly over task space slider trajectory considering a constant cutting speed, the workpiece dimensions and the slider stroke length. Stability of the second-order sliding mode control was validated with the Lyapunov stability theory. Simulations were carried out to verify this approach.
Keywords: switching criterion; constant cutting speed; time-based generator; sliding mode control; singularity points; Slider-crank mechanism